TMET-28. A METHOD FOR EX VIVO STABLE ISOTOPE TRACING IN SURGICALLY EXPLANTED GLIOMA ORGANOIDS. (14th November 2022) - El Shami, Mohamad; Savani, Milan; Gattie, Lauren; Hicks, William; Richardson, Timothy; McBrayer, Samuel; Abdullah, Kalil
Abstract: Stable isotope tracing is a powerful method for elucidating tumor metabolism. While in vivo stable isotope tracing is one of the most faithful approaches for studying metabolic activity under pathophysiologically relevant conditions, this method is technically challenging and costly to perform. We therefore sought to optimize an ex vivo stable isotope tracing approach under conditions that recapitulate the in vivo tumor microenvironment (TME), focusing on three key features: cellular heterogeneity, nutrient availability, and oxygenation. Surgically eXplanted Organoids (SXOs) are 3-dimensional glioma models that retain the diverse cell populations in human brain tumors. We tested whether glioma SXOs can be cultured in Human Plasma-Like Medium (HPLM) under brain-relevant oxygen levels (5%) for the purpose of stable isotope tracing. We cultured SXOs in conventional media, HPLM for 24 hours, or HPLM for 120 hours under 5% oxygen. We observed no significant differences in markers of tumor architecture, cellular proliferation rates, or stemness profiles. We then performed stable isotope tracing in SXOs cultured in HLPM at 5% oxygen. We acclimated SXOs to HPLM for 24 hours or 120 hours before replacing media with either HPLM (unlabeled) or HPLM with 15 N2 glutamine (labeled). 15 N isotopic labeling patterns in various metabolites were compared between the 24- and 120-hour conditions by linear regression. These patterns were strongly concordant over time (r2 = 0.9544), indicating that steady-state metabolic fluxes are stable in these cultures. We then analyzed intermediates that occupy key nodes in amino acid metabolism, redox homeostasis, and nucleotide synthesis pathways and found similarly strong concordance between labeling patterns at the individual metabolite level. Our findings outline an effective approach for conducting ex vivo stable isotope tracing in heterocellular glioma models under conditions that mimic the TME. This approach may complement and enhance analogous in vivo methods to provide new insights into glioma metabolism.